Tanggung Jawab Komisi Penyiaran Indonesia terhadap Glorifikasi Pelaku Pelecehan Seksual pada Media Elektronik - I Kadek Ari Cahya Dwipa; I Nyoman Putu Budiartha; Luh Putu Sudini (Jurnal Konstruksi Hukum, 2022)
With an audiovisual display, it is easy for the audience to know the message conveyed. supervising the administration of local governments in accordance with Article 1 of the Government Regulation of the Republic of Indonesia No. 79 of 2005 concerning Guidelines for the Guidance and Supervision of Regional Government Administration. The Indonesian Broadcasting Commission is an institution that oversees every broadcast that is broadcast with the aim that all broadcasts that are broadcast do not violate the norms that apply in Indonesia. The purpose of this research is to analyze the legal regulation of public broadcasting in electronic media, and to understand the responsibilities of KPI in broadcasting the glorification of sexual harassment perpetrators. This research uses a normative research method using a statutory approach and a conceptual approach in analyzing the problem. The legal regulation on public broadcasting is regulated in Law Number 32 of 2002 concerning Broadcasting which is the main legal material in this research, which supported by legal journals and books. Data collection techniques used are recording and sorting information. In the results of this research, it was found that the Broadcasting Law regulates the issue of legal provisions and regulations regarding broadcasting service providers regarding KPI in charge of regulating matters regarding broadcasting. The Indonesian Supervision Commission has responsibility for glorification cases committed by sexual harassment perpetrators, in accordance with Law No. 32 of 2002 article 8 paragraph (3) concerning broadcasting.